THE EFFECT OF RISK PERCEPTION ON ONLINE PURCHASING DECISIONS IN WEST BANDUNG REGENCY - Sri Surjani Tjahjawati; Dewi Sri Sulastri (Jurnal Ekonomi, 2023)
As internet technology advances, companies may market their products more easily and expand their marketing network. With internet connection, many new things have grown up, including the marketplace. Businesses market their items online with the internet. Risk is caused by unpleasant activities that tarnish consumer impression. Purchase risk perception is a customer response to purchase hazards.  Businesspeople must focus on service quality to reduce risk perception and boost purchasing decisions. This study examines how risk perception affects online product purchases for Shopee customers in West Bandung Regency. A 130-person sample of West Bandung Regency Shopee users was studied. This study used non-probability purposive sampling. Valid and reliable questionnaires were employed to collect data. This study employed simple linear regression. This study found a substantial negative correlation coefficient of -0.534 between risk perception and online shopping decisions. This suggests that consumers buy online more when their risk perception is lower. This study found that risk perception influences purchase decisions by 28.5%, with the regression equation Y = 60.117 - 0.424X.